Nineteenth-Century French Song : Fauré, Chausson, Duparc, and Debussy - Meister, Barbara, 1932- (Book collections on Project MUSE., 1980)
Nowhere in the art song repertoire does one find a more felicitous union than in the 200 or so melodies of Faure, Chausson, Duparc, and Debussy. These four composers brought to the magnificent world of their contemporaries--Verlaine, Gautier, Baudelaire, Mallarme, Leconte de Lisle, and others--the delicacy, sensitivity, and voluptuousness that characterize French music from 1865 to 1914. Song by song, this comprehensive study addresses each composer's complete works for solo, voice, and piano. Errors in popular published editions are pointed out and corrected. The full French text is given, followed by Barbara Meister's translation--in many cases, the first English version ever published. These exquisite renderings (not intended to substitute for the French lyrics in performance) vividly convey the sense and mood of the originals. Here the singer will find guidance on interpretation and pronunciation; the accompanist will profit from harmonic analyses intended to further genuine partnership with the vocalist; and the listener will gain a fuller satisfaction from learning how various works fit into their historical and aesthetic context, and in the lives of the poets and composers.